Vivian Maier self-portraits - Maier, Vivian 1926-2009; Maloof, John (PowerHouse Books, 2013)
With approximately 60 never-before-seen black-and-white and four-color self-portraits culled from the extensive Maloof archive
Includes bibliographical references
Keywords: Maier, Vivian / 1926-2009 / Self-portraits; Maier, Vivian / 1926-2009 / Portraits; Maloof, John / Private collections; Maier, Vivian -- 1926-2009; Portrait photography / Pictorial works; Photography, Artistic; Street photography / Illinois / Chicago; Street photography / New York (State) / New York; Street life / Illinois / Chicago / Pictorial works; Street life / New York (State) / New York / Pictorial works; Selbstbildnis; Fotografie; Bildband